Building blocks of the luxury jewellery industry: conversations with a CEO. Issue 4 (13th March 2019) - Pereira, Beulah; Teah, Kevin; Sung, Billy; Teah, Min
Abstract : Purpose: The purpose of this paper is to conduct an in-depth interview with the Chief Executive Officer (CEO) of Larry Jewelry, a luxury jeweller with boutiques in Hong Kong and Singapore. Given the ever-evolving luxury jewellery market in South East Asia, it is paramount to understand the success factors of the luxury jewellery sector. Design/methodology/approach: An in-depth interview approach is used to understand the antecedents of the success of the luxury jewellery sector. Specifically, this paper presents a complex business model of Larry Jewelry and an in-depth interview with the CEO of Larry Jewelry for current insights in the sector. Findings: This paper highlights the history of Larry Jewelry, its product segments and the key elements of its business blueprint. Specifically, the success of Larry Jewelry is attributed to its business model and strong branding on quality, craftsmanship, rarity, human interaction and trust. Originality/value: Despite the substantial growth in the luxury jewellery sector, there is relatively little research on the success factors of this industry, especially in South East Asia. The current research provides practical insights into business blueprint of a successful luxury jeweller in Hong Kong and Singapore.